Socio-economic Characteristics and Farming Practices of Fish Farmers in Kumbotso Local Government Area of Kano State - Abdul-Azeez, H. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Fish farming business faces numerous challenges that hinder its success. A critical study can help identify these specific challenges. The dearth of information on fish farming activities in Kumbotso Local Government Area hampers our understanding of the constraints facing the industry. This study investigated the socio-economic characteristics, farming practices and local challenges limiting success of fish farming in the area in order to proffer appropriate recommendations. The study area was selected purposively, and data were collected from twenty-six randomly selected fish farmers through questionnaires. Results indicated that the majority of fish farmers are male (100%), married (80.77%), and aged between 31 and 50 years (65.38%). The majority of fish farmers (69.23%) have at least a secondary education, six years of experience in fish farming (57.90%) and considers fish farming as their primary occupation (73.06%). Concrete ponds are predominantly used for fish culture (53.85%), while a significant portion of farmers (30.76%) utilize earthen ponds. African catfish (Clarias gariepinus) is the most farmed species while yield of nearly all the farmers (92.31%) falls less than 10 tonnes per production cycle. A critical examination of the information regarding fish farmers and their activities in the area suggest that the farmers are not fully utilizing their energy and educational potentials to enhance their technical knowledge of the enterprise. Major challenges identified in the area are security, market instability, cold season influence on fish growth, expensive feed and poor road network. Most effective and the immediate measure that should be embarked upon is formation of cooperative societies that would unite efforts of the fish farmers towards overcoming most of the challenges confronting their businesses. Doing this would also provide enabling environment for other stakeholders to easily recognize the farmers’ plight and be willing to offer their contributions